Pemberdayaan Pemuda Ulak Karang Selatan dalam Pembuatan Papan Bunga untuk Menciptakan Entrepeneur - Murdy, Khairi; L.V, Yuhendri; Marna, Jean Elikar; Ritonga, Mentari; Sofyan, Rita; Sofya, Nita (Universitas Pahlawan Tuanku Tambusai, 2026)
Youth empowerment is a crucial issue in national development, particularly in reducing unemployment and increasing their involvement in the economy. In Padang City, the Open Unemployment Rate reached 9.8% in 2024, the highest in West Sumatra Province, contributing to the rise in drug cases, brawls, and gambling in several areas, including Ulak Karang Selatan Village. As a solution, a Community Service program was initiated to empower Karang Taruna (Youth Organization). This program aims to increase the capacity of youth through skills training, namely making contemporary flower boards, to support their economic independence. The approach offered is conducting training and mentoring activities during the service activities. The methods used in the training are lectures, discussions, questions and answers, practice, and guidance. The results of this PKM activity are an increase in participants' understanding of the flower board business and digital marketing. Participants are now able to arrange flowers on acrylic boards, create social media and promotional content to market the flower boards they produce.